2017
DOI: 10.1002/ijgo.12154
|View full text |Cite
|
Sign up to set email alerts
|

Genital Mycoplasma infection among Mexican women with systemic lupus erythematosus

Abstract: One-quarter of women with SLE had genital infection with U. urealyticum. An association was found between infection and multiparity among women with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Infections are a trigger for SLE, and disease activity is linked to Mycoplasma spp. [ 44 ], human papillomavirus [ 45 ] and H. pylori [ 46 ]. The main microorganisms associated with SLE development are Epstein-Barr virus, parvovirus B 19, human T-lymphotropic virus-1, and endogenous retroviruses [ 47 ].…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Infections are a trigger for SLE, and disease activity is linked to Mycoplasma spp. [ 44 ], human papillomavirus [ 45 ] and H. pylori [ 46 ]. The main microorganisms associated with SLE development are Epstein-Barr virus, parvovirus B 19, human T-lymphotropic virus-1, and endogenous retroviruses [ 47 ].…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Previous studies reported maternal diabetes or chronic immune diseases are risk factors for congenital malformation or heart malformation . However, these patients have more frequent vaginal fungal infection compared with the general population and therefore those factors could be considered potential risk factors. However, these potential confounders were not consistent in each study.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study reported a higher incidence of mycoplasmas in the urogenital tract of women with SLE, but the difference was not statistically significant ( Alicja et al, 2020 ). Many previous studies have also claimed that patients with SLE have an increased likelihood of Ureaplasma urealyticum and Mycoplasma hominis infection, two genital mycoplasmas ( Machado et al, 2001 ; Mendez-Martinez et al, 2017 ). M. pneumoniae infection–induced SLE was not presented in these previous studies; thus, it needs further study to confirm its correlation.…”
Section: Discussionmentioning
confidence: 99%